2022
DOI: 10.1021/acscentsci.2c00125
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Recognition of Different Staphylococcus aureus Wall Teichoic Acid Glycoforms

Abstract: Wall teichoic acids (WTAs) are glycopolymers decorating the surface of Gram-positive bacteria and potential targets for antibodymediated treatments against Staphylococcus aureus, including methicillinresistant (MRSA) strains. Through a combination of glycan microarray, synthetic chemistry, crystallography, NMR, and computational studies, we unraveled the molecular and structural details of fully defined synthetic WTA fragments recognized by previously described monoclonal antibodies (mAbs 4461 and 4497). Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The elegant approach of using glycan microarrays-coupled with X-ray crystallography, NMR spectroscopy, and computational studies-revealed that both mAbs recognized the RboP and the GlcNAc residues, and that mAb 4461 specifically recognized a1-4-GlcNAc-modified WTA, while mAb 4497 recognized b1-3-/b1-4-GlcNAc-modified WTAs. 150 Complementary studies have investigated GroP-based WTAs, which are also found in the cell walls of S. aureus and other enterococcus and staphylococcus species. A recent study used microarrays comprised of various synthetic WTA glycans to identify the recognition motif of a mAb (WH7.01) generated by immunization of mice with WH7, a synthetic version of a GroP WTA hexamer.…”
Section: Antibodies To Bacterial Glycansmentioning
confidence: 99%
See 1 more Smart Citation
“…The elegant approach of using glycan microarrays-coupled with X-ray crystallography, NMR spectroscopy, and computational studies-revealed that both mAbs recognized the RboP and the GlcNAc residues, and that mAb 4461 specifically recognized a1-4-GlcNAc-modified WTA, while mAb 4497 recognized b1-3-/b1-4-GlcNAc-modified WTAs. 150 Complementary studies have investigated GroP-based WTAs, which are also found in the cell walls of S. aureus and other enterococcus and staphylococcus species. A recent study used microarrays comprised of various synthetic WTA glycans to identify the recognition motif of a mAb (WH7.01) generated by immunization of mice with WH7, a synthetic version of a GroP WTA hexamer.…”
Section: Antibodies To Bacterial Glycansmentioning
confidence: 99%
“…The elegant approach of using glycan microarrays—coupled with X-ray crystallography, NMR spectroscopy, and computational studies—revealed that both mAbs recognized the RboP and the GlcNAc residues, and that mAb 4461 specifically recognized α1-4-GlcNAc-modified WTA, while mAb 4497 recognized β1-3-/β1-4-GlcNAc-modified WTAs. 150…”
Section: Infectious Diseasementioning
confidence: 99%
“…An antibody against wall teichoic acids (anti-WTA) detects S. aureus more comprehensively but is expensive and synthesis is protected by patent. 7,8 Alternatively, antibiotics conjugated with fluorophores can be used as bacterial detection tools. 9 These small-molecule probes can have significant advantages over antibodies, including better tissue penetration, higher chemical stability, compatibility with antibody-based detection of other biomolecules, and lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…An antibody against S. aureus surface proteins (anti-SA) is commonly applied to detect S. aureus , but exhibits staining heterogeneity due to varying levels of protein expression. An antibody against wall teichoic acids (anti-WTA) detects Gram-positive bacteria more comprehensively, but scaling up experiments using this expensive antibody is rather costly. , Alternatively, antibiotics conjugated with fluorophores can be used as bacterial detection tools . These small-molecule probes can have significant advantages over antibodies, including better tissue penetration, higher chemical stability, compatibility with antibody-based detection of other biomolecules, and lower cost.…”
mentioning
confidence: 99%